Supporting Maintenance of Web Applications Using User-Centered Technique - Siti Nor Asikin, Kamalzaman; Sharifah Mashita, Syed Mohamad; Shahida, Sulaiman; Kamal Z., Zamli (IEEE, 2012)
Maintenance is crucial to ensure delivered software continues to meet its end users’ evolving needs mainly among Web applications’ users. Many approaches and tools have been developed for handling modification requests, of which is the first step of the change management process. However, they lack of functionality to facilitate end users to specify their requests. This limitation causes problems not only to the end users, but to the maintainers as well, who need to understand the requests thoroughly before making any changes. We propose a user-centered technique to support the maintenance process by managing and tracking the modification requests effectively. This paper reports the implementation of the proposed technique as a tool and includes its adoption on a Web application. Initial case study shows that the tool is able to support end users to specify their requests easily and quickly, and maintainers to handle the requests effectively.